Clinically important difference of Stroke-Specific Quality of Life Scale for aneurysmal subarachnoid hemorrhage. (November 2016) - Wong, George K.C.; Lee, Alex; Wong, Adrian; Ho, Faith L.H.; Leung, Sandy L.Y.; Zee, Benny C.Y.; Poon, Wai S.; Siu, Deyond Y.W.; Abrigo, Jill M.; Mok, Vincent C.T.
Highlights: We investigated clinically important differences in Stroke-specific Quality of Life (SS-QOL) for subarachnoid hemorrhage. Over a 2-year period, 65 eligible patients were included in the study. A score change of 4.7 in SS-QOL total score represents a clinically important difference. A score change of 2.1 in SS-QOL physical subscore represents a clinically important difference. A score change of 2.8 in SS-QOL phycosocial subscore represents a clinically important difference. Abstract: Health-related quality of life measurements, are commonly used to quantify burden of disease, to evaluate treatment method, and to facilitate benchmarking. The aim of the current study was to determine the Clinically Important Difference (CID) for a Chinese version of Stroke-specific Quality of Life (SS-QOL) in an aneurysmal subarachnoid hemorrhage (SAH) patient cohort. The study recruited SAH patients in a neurosurgical unit in Hong Kong. SAH patients who completed both 3-month and 1-year assessments were included in the analysis. The study received ethical approvals from the joint CUHK-NTEC Clinical Ethics Committee and written informed consent was obtained from all participants or their next of kins. Over a 2-year period, 65 eligible patients were included in the study. Employing the anchor-based approach with global rating of change, the CID estimate of SS-QOL total score was 4.7 (95% confidence interval [CI]: 2.5–5.3), the CID estimate for SSQOL physical subscore was 2.1 (95% CI: 0.3–2.4), and the CID estimate for SS-QOL psychosocial subscore change was 2.8 (95% CI: 1.8–3.7). In conclusion, our study defined the CID for SS-QOL applied to SAH patients and should be further validated in another SAH patient population.